The ethics of Levinas: the fundamental and essential in nursing care - Gonçalves, Maria Jacirema Ferreira (Revista de Enfermagem UFPE on line, 2011)
Emmanuel Levinas is an original and modern philosopher, which reflection on the ethics of alterity, addresses the duty of care of each one on the Other. The care implies in the knowledge and in to meet the needs of the entity who receives care, giving him the opportunity to care for them and develop their potential. In nursing, the care is their task by formal, legal and ethical definition. However, the question is what is "essential" and what is "fundamental" in the nursing care? Emmanuel Lévinas é um pensador original e moderno, que com sua reflexão sobre a ética da alteridade, aborda o dever do cuidado de cada um perante o Outro. O cuidar caracteriza-se em conhecer e atender as necessidades do ente a ser cuidado, em dar oportunidade a ele de cuidar-se e de desenvolver o seu potencial. Na enfermagem, o cuidado é sua tarefa por definição formal, legal e ética. Entretanto, questiona-se o que é “Essencial” e o que é “Fundamental” no cuidado de enfermagem? <span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-fareast-language: PT-BR;" lang="ES-AR">Emmanuel Levinas es un pensador original y moderno, con su reflexión sobre la ética de la alteridad, se refiere a la obligación de cuidar de cada uno frente al Otro. El cuidado es caracterizado por conocer y satisfacer las necesidades de cuidar del ente, al darle la oportunidad de cuidar de sí mismo y desarrollar su potencial. En la enfermería, el cuidado es su tarea, por definición, formal, legal y ética. Sin embargo, la pregunta es ¿qué es "esencial" y lo que es "fundamental" en los cuidados de enfermería<span style="font-family: Symbol; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-fareast-language: PT-BR; mso-ascii-font-family: 'Trebuchet MS'; mso-hansi-font-family: 'Trebuchet MS'; mso-char-type: symbol; mso-symbol-font-family: Symbol;">?<span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES-AR; mso-fareast-language: PT-BR;" lang="ES-AR">